Hypomorphic mutation in the RAG2 gene affects dendritic cell distribution and migration. Issue 6 (19th September 2013) - Maina, Virginia; Marrella, Veronica; Mantero, Stefano; Cassani, Barbara; Fontana, Elena; Anselmo, Achille; Del Prete, Annalisa; Sozzani, Silvano; Vezzoni, Paolo; Poliani, Pietro Luigi; Villa, Anna
Abstract : In Omenn syndrome, altered dendritic cell distribution and impaired migration represent an additional level of immune dysregulation, contributing to the pathogenesis of autoimmunity. Abstract : OS is a severe combined immunodeficiency characterized by erythrodermia and protracted diarrhea as a result of infiltration of oligoclonal‐activated T cells, caused by hypomorphic mutations in RAGs. The RAG2 R229Q mouse model fully recapitulates the clinical OS phenotype. We evaluated whether T and B cell defects, together with the abnormal lymphoid structure, could affect DC homeostasis and function. High density of LCs was observed in skin biopsies of Omenn patients and in the derma of RAG2 R229Q mice, correlating with the presence of erythrodermia. In vivo models of cutaneous skin painting and CHS demonstrated a decreased migration of RAG2 R229Q DCs—in particular, LCs—into draining LNs. Interestingly, at steady state, RAG2 R229Q mice showed a reduction in DC number in all hematopoietic organs except LNs. Analysis of the MHCII marker revealed a diminished expression also upon the LPS‐driven inflammatory condition. Despite the decreased number of peripheral DCs, BM pre‐cDCs were present in normal number compared with RAG2 +/+ controls, whereas pDCs and monocytes were reduced significantly. Overall, these results point to a secondary defect in the DC compartment, which contributes to clinical manifestations and autoimmunity in OS.